The Falklands War - Eddy, Paul; Linklater, Magnus and Gillman, Peter; Edited By Paul Eddy et all (London Sphere Books Ltd., 1982)
With the sudden Argentine invasion of the remote Falkland Islands on 2 April 1982 the United Kingdom found itself at war. Due to the resolve of a determined Prime Minister and the resourcefulness of the Armed Forces, a Task Force, code named Operation CORPORATE, was quickly dispatched.
Include Index, Maps and Illustrations.
Keywords: Falkland Islands War, 1982 -- Great Britain